2012
DOI: 10.1017/s1074070800000341
|View full text |Cite
|
Sign up to set email alerts
|

Regional Views on the Role of Immigrant Labor on U.S. and Southern Dairies

Abstract: Although immigration is a controversial issue, it is also of major importance to the United States and to agriculture. Immigration policy has been discussed in the recent presidential debates and will likely be debated again in Congress at some point in the near future. Agricultural producer organizations, commodity associations, and lobbying groups have been at the forefront of this issue for many years. Our profession certainly has a role to play by informing constituent groups and the public with objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Among the variance‐reducing factors (in both models 1 and 2) are labor and land. Labor is an important input in dairy farming (Rosson 2012) and plays an important role in production risk management. A closer look at the data reveals that 64% of the total labor hours are paid or hired labor.…”
Section: Resultsmentioning
confidence: 99%
“…Among the variance‐reducing factors (in both models 1 and 2) are labor and land. Labor is an important input in dairy farming (Rosson 2012) and plays an important role in production risk management. A closer look at the data reveals that 64% of the total labor hours are paid or hired labor.…”
Section: Resultsmentioning
confidence: 99%
“…High labor turnover rates or labor shortages can have severe negative consequences for dairy operators, and it is believed that high injury and illness rates contribute to particularly high turnover and limited labor availability in the dairy industry (Hagevoort, Douphrate, and Reynolds 2013). Dairies experienced an average turnover rate of 11.9% in 2008, and farms reported that labor turnover led to reduced production, loss of cows and calves, and reduced herd and feed efficiency (Rosson 2012). Labor shortages are a major concern for most dairy producers.…”
Section: Labor Demand On Dairies and Immigrant Labor Supplymentioning
confidence: 99%
“…More than 20% of farms with at least fifty head of milk cows said that they had experienced a labor shortage between 2007 and 2008 (Rosson et al 2009). Producers typically say that they respond to labor losses by increasing wages, increasing automation, reducing output, relocating their operation, or going out of business (Rosson 2012).…”
Section: Labor Demand On Dairies and Immigrant Labor Supplymentioning
confidence: 99%
“…Dairy farming is nonetheless distinctive from other forms of food production in several crucial respects. First, unlike meatpacking and crop production, which often entail temporary work arrangements and high labor turnover rates, milk production depends on very low labor turnover (Adcock et al ; Mercier ; Rosson ; Schuenemann et al ). As one dairy farmer put it, “the last thing you want to do is bring a new worker into your barn every six months” (Duval qtd.…”
Section: Is Dairy Different?mentioning
confidence: 99%
“…For all of these reasons, skilled workers have proven so essential on dairy farms that even relatively low annual labor turnover rates, ranging from a high of 17.3 percent in the southeastern United States to a low of 9.4 percent in the Midwest (Rosson :273), reduce milk production. In 2014, “both milk production and herd health … decreased by about 1.8 percent as a result of employee turnover, while calf loss and cow death increased by about 1.7 percent and 1.6 percent, respectively” (Adcock et al :11).…”
Section: Quality For Quantitymentioning
confidence: 99%